A Move Structure Analysis of Introduction Sections of Lecturers’ Presentations in English Medium of Instruction (EMI) Classes - Siregar, Zulfathur Ridha; Fauzanna, Wulan (Program Studi Sastra Inggris, 2026)
This study examines the move structure and communicative purposes of introduction sections in lecturers’ presentations in English-Medium Instruction (EMI) classes. The research was conducted in three International Management courses at the Faculty of Economics and Business. A Qualitative method supported by descriptive statistics was used. The data consisted of twelve audio-recorded lecture introductions delivered by three lecturers, analyzed using a move structure framework adapted from Carter (2005), together with the concept of communicative purpose from Swales (1999). A questionnaire was also distributed to 23 students to explore their perspectives on the clarity and engagement of these introductions. The findings show that two main moves, Listener orientation and Content Orientation, appeared in all twelve introductions, indicating that both were obligatory within the dataset. Within Listener orientation, only the greeting step occurred consistently, while within Content Orientation, outlining the lecture structure was the most consistent step. Three new steps were identified: giving announcements, taking attendance, and organizing students' presentations, suggesting that lecturers in this EMI context adapt their introductions to practical classroom demands. Most students (78%) agreed that the introductions given by their lecturers were clear and helped them feel prepared for the lesson. These results suggest that a well-structured introduction is indeed meaningful and supports students' comprehension in EMI classrooms.